Efektivitas Monitoring Sebagai Upaya Meminimalisir Pembiayaan Bermasalah - Alfani, Muhammad; Solihin, Khabib (JIOSE: Journal of Indonesian Sharia Economics, 2023)
Financing is a productive activity carried out by KSPPS (Shari'ah Savings and Loans Cooperative) by channeling funds to members who apply for financing. With the existence of financing activities, it cannot be separated from the existence of financing risks. Non-performing financing is a fatal risk if ignored. So to minimize the risk of problematic financing KSPPS (Shari'ah Savings and Loans Cooperative) needs to have a specific strategy, one of which is financing monitoring. Related to this, this research was conducted to examine how the effectiveness of monitoring in minimizing problem financing. This research is a qualitative descriptive study with the research object of KSPPS BMT Harber Tanggulasi Jepara. The data obtained through interviews, observation and documentation. The collected data were then analyzed using the Miles and Huberman model through three stages, namely data reduction, data presentation, and drawing conclusions. From this study it can be concluded that 1) The implementation of monitoring carried out by KSPPS BMT Harber Tanggulasi Jepara consists of three monitoring, namely indirect monitoring (administrative monitoring), direct monitoring (field monitoring), and follow-up monitoring. 2) Monitoring of problem financing by KSPPS BMT Harber Tanggulasi Jepara has been running effectively, this is evidenced by the decrease in the NPF rate from 15% to 12%. However, the officer in charge of financing must routinely evaluate performance. In order to be able to analyze the problem carefully and field execution can run well.